Variabel-variabel yang Memengaruhi Status Kelayakan Upah Pekerja Perempuan di Provinsi Nusa Tenggara Barat Tahun 2022 - Rahmawati, Aisyah; Setiadi, Yaya (Politeknik Statistika STIS, 2024)
The Provincial Minimum Wage (UMP) is a government policy to realize a living wage for workers. In 2022, 46.12 percent of workers earned less than the UMP. According to the International Labor Organization (ILO), the wages of female workers in Indonesia are 23 percent lower than male workers. Female workers in West Nusa Tenggara (NTB) in 2018-2022 received wages below the UMP. The purpose of this study was to determine the general description, variables and variable trends that affect the wage eligibility status of female workers in NTB in 2022. The test results using binary logistic regression show that the variables of age, education, experience, working hours, and type of work have an effect while the training variable has no effect. The tendency of female workers to have a inadequate wage is those who have a young age, the last education of junior high school / equivalent and below, no training, no experience, working hours are not full-time, and blue-collar jobs. The government should regularly monitor and evaluate UMP policies and improve national education programs.